Targeting poor solubility of docetaxel: Computational screening of ionic liquids using COSMO-RS - Najihah Mohd Noor; Amal A.M. Elgharbawy; Huma Warsi Khan; Yumi Zuhanis Has-Yun Hashim; Muhammad Moniruzzaman; Mohd Firdaus Abd. Wahab; Hamzah Mohd Salleh; Siti Nur Idayu Matusin (Journal of Ionic Liquids, 2025)
Docetaxel (DTX), a chemotherapeutic agent widely used in cancer treatment, has limited therapeutic efficacy owing to its poor oral absorption and low bioavailability. This study aims to improve DTX solubility by predicting its compatibility with ionic liquids (ILs) using conductor-like screening model for real solvents (COSMO-RS) computational modelling. A library of 340 ILs comprising 17 cations and 20 anions was screened for their potential to dissolve DTX, with a particular focus on imidazolium-based ILs that enhance its solubility and pertinence to cytotoxic applications. Computational analysis identifies ILs containing cations such as 1-methylimidazolium [MIM] and 1,3-dimethylimidazolium [DMIM] and anions such as [CH3COO–], [Br–], and [Cl–], which have high solubility potential for DTX. Parameters such as the activity coefficient, solubility, capacity, selectivity, and performance index were evaluated. The σ-profile of DTX shows a predominantly nonpolar surface with limited hydrogen bond acceptor regions, indicating that its solubility in ILs is primarily driven by nonpolar (dispersion) interactions, with minor contributions from hydrogen bonding. Although these findings identify several promising IL candidates for improving the solubility of DTX, experimental validation is essential to confirm these computational predictions and assess the suitability of selected ILs in pharmaceutical formulations. This study demonstrates the value of COSMO-RS as a predictive tool for pharmaceutical formulation design and provides a pathway to enhance drug delivery for chemotherapeutics with poor solubility.